KOMODIFIKASI PEKERJA PADA YOUTUBER PEMULA DAN UNDERRATED (Studi Kasus YouTube Indonesia) - Ulya, Himmatul (Interaksi: Jurnal Ilmu Komunikasi, 2019)
The purpose of this research is to reveal commodification form and process which experienced by beginner and underrated YouTuber in Indonesia. This research uses a critical paradigm with qualitative approach through observation and indepth interview by developing political economy communication through especially commodification of labor as a theoritical framework. The development of new media especially YouTube, became on of the attractions for the community to plunge as creative workers in the digital world. YouTuber also known as content creator is profession that is in great demand by the millenial generation it can upload content video that can provide commercial benefits and popularity. The monetization and copyright feature on the YouTube platform was not able to be obtained by all creators. This research shows the commodification process that is not realized by creators, especially beginner and underrated YouTuber through the YouTube partnership programs (YPP). The commodification form experienced by creators is the exploitation of content ownership and digital labor. Hence, creators and YouTubers accept the exploitation as a fair demand because of process alienation, mystification, reification and naturalization.